2017
DOI: 10.4172/2155-952x.1000256
|View full text |Cite
|
Sign up to set email alerts
|

Use of Agro Industrial Residues for the Production of Amylase by Penicillium sp. for Applications in Food Industry

Abstract: Glucoamylase production has been investigated by solid state fermentation using agro-industrial residues, rice bran, wheat bran and banana peel by Penicillium sp. Out of the different agricultural residues tested for enzyme production, rice bran yielded the maximum glucoamylase activity (10.29 ± 0.07 Units/ml), protein content (1.22 ± 0.0014 mg/ml) and specific activity (8.4 Units/mg protein) with Penicillium sp. after 7th day of fermentation as compared to other agro residues. Media supplementation with carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The optimum fermentation period for enzyme production was 7 days with wheat bran ,while with rice bran ,corn bran and potato waste it was 9 ,7 and 9 days ,respectively .Using wheat bran , rice bran ,corn bran and potato waste enzyme production by Penicillium sp(3) at the optimum time of incubation was 320.49 ,82.68 ,134.85 and 97.98 IU/ g , respectively. Fermentation medium consists of 5gm agricultural by -producte ,5ml tap water , incubation performed at 28 °C Results on Penicillium sp.isolates are in agreement with results obtained by Arora et al,(2017),who found that the maximum production of glucoamylase by Penicillium sp, using rice bran ,wheat bran and banana peel as agro industrial wastes ,was obtained after 7 days of incubation .On the other hand ,they found that rice bran proved to be the best waste for enzyme production by Penicillium sp, followed by wheat bran and banana peel .…”
Section: Data Insupporting
confidence: 87%
“…The optimum fermentation period for enzyme production was 7 days with wheat bran ,while with rice bran ,corn bran and potato waste it was 9 ,7 and 9 days ,respectively .Using wheat bran , rice bran ,corn bran and potato waste enzyme production by Penicillium sp(3) at the optimum time of incubation was 320.49 ,82.68 ,134.85 and 97.98 IU/ g , respectively. Fermentation medium consists of 5gm agricultural by -producte ,5ml tap water , incubation performed at 28 °C Results on Penicillium sp.isolates are in agreement with results obtained by Arora et al,(2017),who found that the maximum production of glucoamylase by Penicillium sp, using rice bran ,wheat bran and banana peel as agro industrial wastes ,was obtained after 7 days of incubation .On the other hand ,they found that rice bran proved to be the best waste for enzyme production by Penicillium sp, followed by wheat bran and banana peel .…”
Section: Data Insupporting
confidence: 87%
“…Amongst rice bran, wheat bran and banana peel, the SSF of rice bran by Penicillium sp. showed the highest glucoamylase activity (10.29 units mL −1 ) 77 . In an attempt to produce cellulases using SSF by Pleurotus ostreatus , higher cellulase activity was reported with rice husk than wheat straw 78 .…”
Section: Strategies For Valorization Of Crop Residuesmentioning
confidence: 95%
“…showed the highest glucoamylase activity (10.29 units mL −1 ). 77 In an attempt to produce cellulases using SSF by Pleurotus ostreatus, higher cellulase activity was reported with rice husk than wheat straw. 78 Nevertheless, the SSF of industrial enzymes has not been implemented at full scale.…”
Section: Industrial Enzymesmentioning
confidence: 99%